Little Egret and Toro - Vavra, Robert; Short, John (San Rafael, Calif. : Channel Photographics, 2010)
The egret warns the bull that he will wind up in the butcher shop if he goes into the bullring; so when he does fight, the bird devises a plan to save him.
"First published by William Collins Sons Co. Ltd. London 1966"--T.p. verso.
2.4
K-3
K-3
Keywords: Bullfights -- Juvenile fiction; Herons -- Juvenile fiction; Bullfights -- Fiction; Herons -- Fiction; Bullfights -- Fiction; Herons -- Fiction